Contextualizing the COVID-19 Era in Puerto Rico: Compounding Disasters and Parallel Pandemics - García, Catherine (J Gerontol B Psychol Sci Soc Sci, 2020)
OBJECTIVES: The COVID-19 outbreak has worsened the ongoing economic crisis in Puerto Rico by creating “parallel pandemics” that exacerbate socioeconomic and health inequalities experienced by its most vulnerable residents. Unfortunately, conditions on the island have been largely overlooked by national media outlets and the mainland U.S. population. Thus, this research report aims to draw attention to the disparate burden multiple and compounding disasters have on older island-dwelling Puerto Rican adults’ health and well-being. METHODS: We characterize the lived experiences of the older population in Puerto Rico by incorporating data from multiple sources and contextualizing the effects of compounding disasters, the fiscal pandemic, and health care challenges to provide a more nuanced portrait of existing compounding factors that negatively affect the health and well-being of older adults in the era of COVID-19. RESULTS: We highlight 2 main factors that exacerbate pre-pandemic inequities experienced by the older adult population amid the COVID-19 pandemic in Puerto Rico: (a) the impact of multiple and compounding disasters; and (b) health care challenges. DISCUSSION: The human suffering of the Puerto Rican population is compounded by the consequences of fiscal austerity, increasing levels of income and wealth inequality, the debt crisis, significant emigration, and a dysfunctional health care system. Future governmental actions are required to lessen the burden of parallel pandemics on older adults in Puerto Rico.